Morbidity profile and outcome of low-birth-weight neonates in NICU of a tertiary care hospital - Chauhan, Anuya V.; Gosai, Dhara; Patel, Urvi (International Journal of Contemporary Pediatrics, 2022)
Background: Birth weight has been accepted as the most important reliable index of the health status of the community and is an indicator of neonatal morbidity and mortality. Aims and objectives were to determine the incidence, clinical and epidemiological profile of low-birth-weight (LBW) neonates in NICU in tertiary care settings and to assess the distribution of various morbidities, mortalities and outcome based on the weight of the neonates. Methods: This hospital-based prospective study was conducted for one year in NICU at a tertiary care centre, Ahmedabad. All neonates with birth weight <2.5 kg admitted in NICU were included in study. Data on gestational age and birth weight, congenital anomalies, morbidities and mortalities along with their outcomes was collected and analysed. Results: Total admissions in NICU over a period of one year of the tertiary care centre, Ahmedabad were 4275 of which 64.63% were LBW. The maximum number among the LBW of the new-borns (72.47%) were having a birth weight ranging from 1500-2499 gm. The sex ratio was 1.46:1, indicating males (59.39%) more than females (40.61%) NICU stay of the babies in <1 kg, 1 to 1.499 kg and 1.5 kg were maximum at 8 to 10 days. The main cause of mortality in <1 kg and 1-1.499 kg babies were prematurity. Conclusions: The prevalence of LBW neonates accounted for 64.63% of NICU admission. Common morbidities observed in LBW babies were perinatal asphyxia, RDS/HMD, jaundice. The early outcome was that 46.9% of babies were discharged while 39.3%.